Problematika Penerapan Aturan Pembatasan Hak Asasi Manusia Dalam Konstitusi Indonesia - Galuh Candra Purnamasari (Jurnal Hukum PRIORIS, 2017)
After the amendment, the constitutionality of human rights was realized in chapter X article 28A-28J, which shows that Indonesia is increasingly upholding human rights values with the transformation of these rights in the constitution. However, this is still debatable about the provision of non-derogable rights (Article 28I) and human rights limitation (Article 28J). Human rights that could be limited is human right which is categorized in derogable right. The problem is the failure to distinguish between human rights which its implementation could be limited and vice versa. This condition is exacerbated by systematic and conceptual errors in chapter X of the 1945 Constitution, which can cause problems in applying the provision of human rights restrictions, and in implementing the interpretation of the human rights restrictions by Constitutional Court. This paper used normative legal research with literature research. This paper find that that the implementation of human rights limitation in Indonesia has not been in accordance with the theories and principles of human rights law and is carried beyond the supposed.